Association between the systemic inflammation response index and mortality in the asthma population - Xu, Feng; Jiang, Hui; Li, Fanglan; Wen, Yan; Jiang, Pan; Chen, Feng; Feng, Yongwen (Frontiers in Medicine, 2024)
Background As a novel indicator of inflammation, the relationship between the systemic immune-inflammation index (SIRI) and mortality in patients with asthma remains uncertain. Our study aimed to explore the association between SIRI and mortality in asthma patients. Methods Data from the National Health and Nutrition Examination Survey (NHANES) for US adults from 2001 to 2018 were included in this study. Then, we divided all patients into three groups based on SIRI tertiles and used multivariable weighted Cox regression analysis, smoothing curve fitting, survival curve analysis, and subgroup analysis to investigate the relationship between SIRI and asthma. Results A total of 6,156 participants were included in the study, with each SIRI tertile consisting of 2052 individuals. Asthma patients with higher SIRI levels were older, had a higher level of education, were more likely to be married, and had a higher chance of being smokers. In Cox proportional-hazards models, the highest SIRI group showed higher hazard ratios (HRs) for all-cause mortality in individuals with asthma after adjusting for potential confounders. The restricted cubic spline analysis indicated a non-linear relationship between SIRI and all-cause mortality. The Kaplan–Meier survival curves showed that patients with higher SIRI levels had a higher risk of all-cause mortality. Subgroup analyses revealed SIRI’s association with all-cause mortality across various demographics, including age, sex, race, education levels, smoking status, and marital status. Conclusion Our study provides evidence for the relationship between SIRI and mortality in asthma patients. SIRI may potentially serve as a predictive tool for evaluating asthma mortality rates.